The career agency of indian managerial women: a culture-centred approach. - Prashar, Manjari (Cranfield University, 2018)
The purpose of this study is to develop a culturally sensitive model of women’s career agency. Adopting a qualitative research method, analyzing semi structured interviews with 36 managerial women in India this study provides a culture' centred model of career agency and a culture' centred framework for the analysis of career agency. The model highlights how managerial women’s career agency interacts with the enabling and constraining aspects of the context in which their careers unfold. This study broadens our understanding of women’s career agency by revealing the dynamic relationship between the context and the individual as emergent ‘agentic bonds’ shifting over time and in relation to each other. Career agency is conceptualized as a process of emergent agentic bonds within a temporal relational context. This study identifies five agentic bonds fusion, communion, divergence, assertion and integration through which individual assert agency in their careers. The study makes three contributions. First, a theoretical contribution introducing a career centred model of career agency. This model identifies the construct of ‘agentic bonds’, to distinguish the ways in which individual’s bond with the collective to develop career intentions and actions. This new construct facilitates a culturally sensitive view of career agency as a contextually dependent process, extending Stage theories of careers beyond Individual agency. In addition, a sub contribution of a culture centred framework for the analysis of agency in women’s careers, operationalizing and is aggregating career agency permits a liminal/hybrid/fluid view of agency and extends the theory of culture centred approach to careers. Second, an empirical contribution reconciling and resolving the struggle to identify the career agency of Indian managerial women. Third, a practical contribution with a culturally sensitive approach to career coaching embedded in a temporal relational view of career agency, facilitated by the concept of ‘agentic bonds’. The study responds to the call for cultural sensitivity in careers research and practice.
Keywords: Agentic bonds; temporal-relational context; subaltern agency; individual agency; collective agency